KEPATUHAN MINUM OBAT, PEMBATASAN CAIRAN, DIET RENDAH GARAM (NATRIUM) PADA PASIEN YANG MENJALANI HEMODIALISIS RUTIN DI SATU RUMAH SAKIT TANGERANG - Kusman Sudarja; Grace Alesia Pandiangan; Grace Putri Nababan; Intan Elfira Febrieni Zebua; Eva Chris Veronica Gultom (Jurnal Keperawatan Malang, 2025)
Background: Chronic kidney disease is a disease with an increasing incidence every year. The implications of kidney failure are associated with routine hemodialysis therapy. Implementing this therapy requires discipline in adherence to medication, fluid restriction, and a low-salt (sodium) diet. Purpose: identify medication adherence, fluid restriction, and a low-salt (sodium) diet in patients undergoing routine hemodialysis at a Tangerang hospital. Methods: This study used a quantitative descriptive design and a cross-sectional approach. A sample size of 139 patients undergoing routine hemodialysis was selected using a convenience sampling technique. A questionnaire was used as the measurement tool. Data analysis used univariate analysis. Result: Among patients undergoing routine hemodialysis at a Tangerang hospital, the majority were moderately compliant with medication (74.1%), with a majority compliant with fluid restriction (51.1%), and a majority compliant with a low-salt (sodium) diet (53.2%). Implication: This study demonstrates the need for improved health education and patient support, particularly regarding medication adherence, which is still moderate. Continuous nursing interventions are essential to prevent complications and improve the quality of life of hemodialysis patients. Further research with an analytical design is needed to identify factors influencing hemodialysis patient adherence Keywords: Low-salt (sodium) diet; Hemodialysis; Compliance; Medication intake; Fluid restriction